Optimal Use of Raltegravir (Isentress®) in the Treatment of HIV-Infected Adults – Canadian Consensus Guidelines - Anita Rachlis; Jonathan B Angel; Marianne Harris; Stephen D Shafran; Rachel Therrien; Cécile Tremblay; Mark A Wainberg (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND AND OBJECTIVES: A meeting of a Canadian group with significant experience and knowledge in HIV management, consisting of five physicians, a pharmacist and an AIDS researcher, was convened. Their goal was to develop guidance for Canadian HIV-treating physicians on the appropriate use of raltegravir (MK-0518, Isentress®, Merck Frosst Canada Inc) in HIV-infected adults.